2013
DOI: 10.2174/1389202911314030001
|View full text |Cite
|
Sign up to set email alerts
|

Compatible Solute Engineering in Plants for Abiotic Stress Tolerance - Role of Glycine Betaine

Abstract: Abiotic stresses collectively are responsible for crop losses worldwide. Among these, drought and salinity are the most destructive. Different strategies have been proposed for management of these stresses. Being a complex trait, conventional breeding approaches have resulted in less success. Biotechnology has emerged as an additional and novel tool for deciphering the mechanism behind these stresses. The role of compatible solutes in abiotic stress tolerance has been studied extensively. Osmotic adjustment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(74 citation statements)
references
References 84 publications
1
62
0
Order By: Relevance
“…Osmotic regulation is an effective measure for plants to adapt to osmotic stress and avoid dehydration. Organic solutes or osmoprotectants aid plant survival under extreme stress via osmotic adjustment by stabilizing specific proteins and membranes and by preventing dehydration within the organelles of cells [68][69][70]. To adapt to salt stress, most of the glycophytes, including cotton, accumulate a large number of organic solutes in their tissues [71].…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic regulation is an effective measure for plants to adapt to osmotic stress and avoid dehydration. Organic solutes or osmoprotectants aid plant survival under extreme stress via osmotic adjustment by stabilizing specific proteins and membranes and by preventing dehydration within the organelles of cells [68][69][70]. To adapt to salt stress, most of the glycophytes, including cotton, accumulate a large number of organic solutes in their tissues [71].…”
Section: Discussionmentioning
confidence: 99%
“…One of these osmoprotectants, glycine betaine, is a bipolar quaternary ammonium compound, which accumulates in many plant species when subjected to various abiotic stresses (Rhodes and Hanson, 1993;Fan et al, 2012). Glycine betaine protects the plant from salt stress by maintaining the osmotic balance under various abiotic stresses (Wani et al, 2013) and by stabilizing the quaternary structure of complex proteins (Bernard et al, 1988). In photosynthetic systems, glycine betaine stabilizes the oxygen-evolving photosystem II complex and Rubisco at elevated salt concentrations (Zhou et al, 2008;Fan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The BADH gene has been cloned from Spinacia oleracea (Weretilnyk and Hanson, 1990), Atriplex hortensis (Xiao et al, 1995), Beta vulgaris (McCue and Hanson, 1992), Sorghum bicolor (Wood et al, 1996), Carthamus tinctorius (Wang et al, 2014), and Avicennia marina, and its functions are well characterized (Hibino et al, 2001). However, many researchers have demonstrated that some plant species, such as Arabidopsis, tobacco, tomato, and rice, do not accumulate glycine betaine (Huang et al, 2000;Sakamoto and Murata, 2000;Wani et al, 2013). This has generated interest in the metabolic engineering of the glycine betaine biosynthesis pathway as an approach to enhance salt resistance in salt-sensitive species .…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress, a major limiting factor for turfgrass management in many regions , results in a buildup of reactive oxidative species in plant cells and damages protein structures and cell membranes; drought-induced osmotic stress may also occur in most plants (Ashraf, 2010;Reddy et al, 2004). To cope with drought stress, plants store multiple groups of compatible metabolites such as betaines, proline, and sugar alcohols (Dawood et al, 2014;Hussain Wani et al, 2013). It has been well established that GB plays an important role in defensive mechanisms, maintaining osmotic balance; stabilizing the structure and function of proteins, enzymes, and membranes; and inducing resistance-related gene expression (Bohnert and Jensen, 1996;Hussain Wani et al, 2013;Rathinasabapathi, 2000;Saneoka et al, 1995).…”
mentioning
confidence: 99%
“…To cope with drought stress, plants store multiple groups of compatible metabolites such as betaines, proline, and sugar alcohols (Dawood et al, 2014;Hussain Wani et al, 2013). It has been well established that GB plays an important role in defensive mechanisms, maintaining osmotic balance; stabilizing the structure and function of proteins, enzymes, and membranes; and inducing resistance-related gene expression (Bohnert and Jensen, 1996;Hussain Wani et al, 2013;Rathinasabapathi, 2000;Saneoka et al, 1995). It has been reported that exogenous application of GB could alleviate the damage of abiotic stress (i.e., salt, drought, and heat stress) in various crop plants and turfgrass (Burgess and Huang, 2014;Malekzadeh, 2015;Maziah and Teh, 2016;Raza et al, 2014).…”
mentioning
confidence: 99%